Tonsillectomy or adenotonsillectomy versus non-surgical management for obstructive sleep-disordered breathing in children - Venekamp, Roderick P; Hearne, Benjamin J; Chandrasekharan, Deepak; Blackshaw, Helen; Lim, Jerome; Schilder, Anne G M (Cochrane database of systematic reviews, 2015)
Obstructive sleep-disordered breathing (oSDB) is a condition that encompasses breathing problems when asleep, due to an obstruction of the upper airways, ranging in severity from simple snoring to obstructive sleep apnoea syndrome (OSAS). It affects both children and adults. In children, hypertrophy of the tonsils and adenoid tissue is thought to be the commonest cause of oSDB. As such, tonsillectomy - with or without adenoidectomy - is considered an appropriate first-line treatment for most cases of paediatric oSDB. To assess the benefits and harms of tonsillectomy with or without adenoidectomy compared with non-surgical management of children with oSDB. We searched the Cochrane Register of Studies Online, PubMed, EMBASE, CINAHL, Web of Science, Clinicaltrials.gov, ICTRP and additional sources for published and unpublished trials. The date of the search was 5 March 2015. Randomised controlled trials comparing the effectiveness and safety of (adeno)tonsillectomy with non-surgical management in children with oSDB aged 2 to 16 years. We used the standard methodological procedures expected by The Cochrane Collaboration. Three trials (562 children) met our inclusion criteria. Two were at moderate to high risk of bias and one at low risk of bias. We did not pool the results because of substantial clinical heterogeneity. They evaluated three different groups of children: those diagnosed with mild to moderate OSAS by polysomnography (PSG) (453 children aged five to nine years; low risk of bias; CHAT trial), those with a clinical diagnosis of oSDB but with negative PSG recordings (29 children aged two to 14 years; moderate to high risk of bias; Goldstein) and children with Down syndrome or mucopolysaccharidosis (MPS) diagnosed with mild to moderate OSAS by PSG (80 children aged six to 12 years; moderate to high risk of bias; Sudarsan). Moreover, the trials included two different comparisons: adenotonsillectomy versus no surgery (CHAT trial and Goldstein) or versus continuous positive airway pressure (CPAP) (Sudarsan). Disease-specific quality of life and/or symptom score (using a validated instrument): first primary outcomeIn the largest trial with lowest risk of bias (CHAT trial), at seven months, mean scores for those instruments measuring disease-specific quality of life and/or symptoms were lower (that is, better quality of life or fewer symptoms) in children receiving adenotonsillectomy than in those managed by watchful waiting:- OSA-18 questionnaire (scale 18 to 126): 31.8 versus 49.5 (mean difference (MD) -17.7, 95% confidence interval (CI) -21.2 to -14.2);- PSQ-SRBD questionnaire (scale 0 to 1): 0.2 versus 0.5 (MD -0.3, 95% CI -0.31 to -0.26);- Modified Epworth Sleepiness Scale (scale 0 to 24): 5.1 versus 7.1 (MD -2.0, 95% CI -2.9 to -1.1).No data on this primary outcome were reported in the Goldstein trial.In the Sudarsan trial, the mean OSA-18 score at 12 months did not significantly differ between the adenotonsillectomy and CPAP groups. The mean modified Epworth Sleepiness Scale scores did not differ at six months, but were lower in the surgery group at 12 months: 5.5 versus 7.9 (MD -2.4, 95% CI -3.1 to -1.7). Adverse events: second primary outcomeIn the CHAT trial, 15 children experienced a serious adverse event: 6/194 (3%) in the adenotonsillectomy group and 9/203 (4%) in the control group (RD -1%, 95% CI -5% to 2%).No major complications were reported in the Goldstein trial.In the Sudarsan trial, 2/37 (5%) developed a secondary haemorrhage after adenotonsillectomy, while 1/36 (3%) developed a rash on the nasal dorsum secondary to the CPAP mask (RD -3%, 95% CI -6% to 12%). Secondary outcomesIn the CHAT trial, at seven months, mean scores for generic caregiver-rated quality of life were higher in children receiving adenotonsillectomy than in those managed by watchful waiting. No data on this outcome were reported by Sudarsan and Goldstein.In the CHAT trial, at seven months, more children in the surgery group had normalisation of respiratory events during sleep as measured by PSG than those allocated to watchful waiting: 153/194 (79%) versus 93/203 (46%) (RD 33%, 95% CI 24% to 42%). In the Goldstein trial, at six months, PSG recordings were similar between groups and in the Sudarsan trial resolution of OSAS (Apnoea/Hypopnoea Index score below 1) did not significantly differ between the adenotonsillectomy and CPAP groups.In the CHAT trial, at seven months, neurocognitive performance and attention and executive function had not improved with surgery: scores were similar in both groups. In the CHAT trial, at seven months, mean scores for caregiver-reported ratings of behaviour were lower (that is, better behaviour) in children receiving adenotonsillectomy than in those managed by watchful waiting, however, teacher-reported ratings of behaviour did not significantly differ.No data on these outcomes were reported by Goldstein and Sudarsan. In otherwise healthy children, without a syndrome, of older age (five to nine years), and diagnosed with mild to moderate OSAS by PSG, there is moderate quality evidence that adenotonsillectomy provides benefit in terms of quality of life, symptoms and behaviour as rated by caregivers and high quality evidence that this procedure is beneficial in terms of PSG parameters. At the same time, high quality evidence indicates no benefit in terms of objective measures of attention and neurocognitive performance compared with watchful waiting. Furthermore, PSG recordings of almost half of the children managed non-surgically had normalised by seven months, indicating that physicians and parents should carefully weigh the benefits and risks of adenotonsillectomy against watchful waiting in these children. This is a condition that may recover spontaneously over time.For non-syndromic children classified as having oSDB on purely clinical grounds but with negative PSG recordings, the evidence on the effects of adenotonsillectomy is of very low quality and is inconclusive.Low-quality evidence suggests that adenotonsillectomy and CPAP may be equally effective in children with Down syndrome or MPS diagnosed with mild to moderate OSAS by PSG.We are unable to present data on the benefits of adenotonsillectomy in children with oSDB aged under five, despite this being a population in whom this procedure is often performed for this purpose.